Pedagogical tasks for collaborative digital storytelling creation: Practical design and implementation - Ferdiansyah, Sandi (Beyond Words, 2019)
This article demonstrates a step by step into digital stories creation in a language classroom that teachers may adapt or adopt for their classroom purposes. At the outset, it will explore the nature of digital storytelling and empirical evidence of digital storytelling implementation across levels. Additionally, the article proposes ideas on how collaborative learning can be integrated in the making of digital storytelling. The design and implementation of pedagogical task emphasize on giving more opportunities for students to engage in the genre based collaborative digital stories project and foster their critical thinking and creativity. At the end of this article, alternative assessment is promoted to assess the learning process as well as the students’ project of digital storytelling. Providing students with scaffolded activities, I contend that every language teacher now can empower their learners to become digital storytellers.